THE ROLE OF MOBILE INSTANT MESSENGER AS SUPPORTIVE PLATFORM FOR MEDICAL CAREER INTERVENTION - Rizma Adlia Syakurah; Yayi Suryo Prabandari; Doni Widyandana; Amitya Kumara (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Career intervention in medical students is an activity meant to increase awareness and early exposure on various medical careers. Utilization of technology as a support to career intervention model offers a novel approach that might optimize the exposure and quality of the intervention and can be developed as a safe and non-judgemental environment for the students to talk about career-related topics. Aims: This study aimed to determine the use of mobile instant messenger as a supportive tool for medical career intervention. Learning Media Review: LineTM is a mobile instant messenger platform that is used to communicate and send messages using the internet. This platform provides voice and video calls, text messages, polls, and other features such as: stickers, photos, videos, voice messages, and location. These features can be accessed free of charge by users. This article uses discussion and participatory observation methods for three weeks. Thirty six (n=36) first-year medical students that were joining a career introduction course were placed into on online group, a LineTM group, led by two facilitators to guide their daily discussion. The responses are voluntary and they were encouraged to express themselves freely without any topic restriction whatsoever throughout the sessions. Online transcripts were then coded according to recurring topics and themes that came up during their discussions. Eight themes were identified from the discussion and categorised into three: 3 major categories, 2 intermediate and 3 minor. Major themes identified were role model, non-academic career information, and clinical clerkship. This study show maximum engagement of 26 participants on first day with maximum discussion length in one topic of three hours during career-related topics. Conclusion: Mobile instant messaging is considered useful in supporting a medical career intervention, especially in providing career information and carrying a momentum for career-related discussion. It is further stated that the role of online facilitator as a peer mentor is major in providing quality discussion, a safe environment, and accurate source of information to the students.